Cellular and molecular mechanisms underlying root sucker formation in Arabidopsis lyrata - Silva, Thaís Cristina Ribeiro da (2017)
Shoot organogenesis from roots (root suckers) allows vegetative propagation of Arabidopsis lyrata, the closest relative of Arabidopsis thaliana, in addition to sexual propagation and is an important trait associated with the root system. Using an in vitro system, we aimed to better understand the vegetative propagation in the model species A. lyrata, in what regards the morphological development of root suckers, the ability of vegetative propagation in different in vitro growth conditions, and identifying genes potentially involved in the formation of the new shoot apical meristem.Root sucker appearanceoccurred after30 days,most frequently in the axils of lateral roots. Root cross-sections showed a typical diarch primary structure and after 25 days, secondary root growth could be observed, as indicated by formation of the cambium. According to our data,root sucker emergence resembles the initiation of lateral roots from the pericycle, the tissue that gives rise to the vascular cambium during secondary growth. Regarding the in vitro growth conditions, full strength of MS induced the highest number of root suckers per plant, followed 3% of sucrose. However, light exposure and sucrose deprivation are not strictly required for sucker formation. Our data also revealed that auxin promotes root suckering. Vascular auxin response maxima are required to trigger lateral root initiation, suggesting that auxin- promoted sucker formation likely occurs by similar mechanisms. The evaluation of different shoot apical meristem related genes, suggests that the STM gene can be a potential marker to identify cells responsible in driving sucker formation. Arabidopsis lyrata proved to be an excellent model for further studies using root suckers, for example to study epigenetic marks throughout generations of clonal propagation.